Effects of the Power Card Strategy on Social Commenting of Children with Autism During Gameplay: Strength-Based Intervention. (July 2023) - Prince, Julia; Tincani, Matt; Dowdy, Art
Children with autism spectrum disorder (ASD) experience challenges with social interactions that manifest in specific social situations. These challenges may inhibit them from developing sustained friendships with school-age peers, resulting in their exclusion from group-based leisure activities. To aid this population in developing friendships, there is a crucial need to evaluate interventions designed to teach social skills during group-based leisure activities. The power card strategy (PCS) is a strength-based intervention that incorporates a child's special interest to help them navigate challenging social situations. Using a multiple-probe design, we evaluated the effects of the PCS with three students diagnosed with ASD who displayed difficulty with social commenting during group-based leisure activities. For all three individuals, the PCS resulted in increased appropriate social comments during game play that included both taught and novel comments. These findings maintained over time and generalized to a novel gaming activity with classmates in the community.